Hubungan antara Perilaku Asertif dan Feminisme dengan Kekerasan Berbasis Gender Online pada Peserta Didik Sekolah Menengah Atas - Ananda Febrilina Subiantara; Retno Tri Hariastuti; Eko Darminto (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research aims to find out the relationship between assertive behavior and feminism with online gender-based violence in senior high school students. The results of this research can be used as a reference by guidance and counseling teachers to provide counseling services to perpetrators of gender-based violence that happens to senior high school students. The type of data used in this research was quantitative data. Quantitative data were analyzed using normality test, linearity test, and hypothesis test. Based on the normality test, Assertive behavior and feminism are normally distributed because the significant value is lower than 0.05. The data from the linearity test results show that the feminism variable has a linear relationship to OGBV. The magnitude of the contribution of Assertive Behavior and Feminism with Online Gender-Based Violence has the strongest relation to influence preventing adolescents from acting on OGBV, namely feminism by 32%, while the effect of assertive behavior on preventing adolescents from acting on KBGO is 0.7%. The conclusion of this study is that assertive behavior and feminism have a relationship with OGBV and feminism has a more significant influence on OGBV compared to assertive behavior. The influence of feminism is 32%, while the influence of assertive behavior on preventing students from acting on OGBV is by 0,07%.